The Use of Reproductive Biotechnology to Achieve Genetic Improvement in Cattle - Adriana M Lubis (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2000)
Reproductive biotechnology has many potential uses. It can be used to increase the rate of genetic improvement, but they have the potential to cause an even greater increase in the rate of inbreeding. Determining how to gain genetic advantage from these technologies, while at the same time minimizing their genetic disadvantage, has provided a major challenge for geneticists. Multiple ovulation and embryo transfer (MOET), in vitro embryo production (IVEP) only produce substantial increases in the rate of genetic improvement, with acceptable rates of inbreeding. In contrast, semen sexing, embryo sexing reduces the numbers of the other sex, the effect is negligible and only will have a marginal effect on the rate of improvement. They can produce only limited increase of the rate of genetic improvement. There will be great interdependence between the techniques, the way in which the use of a new technique will depend upon which of the other procedures are available. There is a need for research not only to  establish the techniques, but also to  consider the best use of them in  animal breeding and production schemes. Nevertheless, the ethicist might play an important role as a guide in moral decision making and training for a morally responsible attitude. The aim of this paper is to review the ways in which these technologies can be used to increase genetic improvement in cattle.  Key words : MOET, IVEP, semen sexing, embryo sexing